Belting, H. (2011). Florence & Baghdad : Renaissance Art and Arab Science. Cambridge MA: Harvard University Press, 312 p. - Kwiatkowski, Nicolás (Universidad Nacional de San Martín. UNSAM Edita, 2014)
Artículo de anuario